2005
DOI: 10.1523/jneurosci.0277-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pedunculopontine Tegmental Nucleus Controls Conditioned Responses of Midbrain Dopamine Neurons in Behaving Rats

Abstract: Midbrain dopamine (DA) neurons respond to sensory cues that predict reward. We tested the hypothesis that projections from the pedunculopontine tegmental nucleus (PPTg) are involved in driving this DA cell activity. First, the activity of PPTg and DA neurons was compared in a cued-reward associative learning paradigm. The majority of PPTg neurons showed phasic responses to the onset of sensory cues, at significantly shorter latency than DA cells, consistent with a PPTg-to-DA transmission of information. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
172
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(191 citation statements)
references
References 46 publications
18
172
1
Order By: Relevance
“…There have been only a few studies examining visual responses of PPTN neurons. Pan & Hyland (2005), reported visual responses of PPTN neurons in rats, which had a mean response latency to the onset of a light stimulus of 70 ms, but they observed no variable visual responses for reward prediction (Pan & Hyland, 2005). In contrast to these results, a population of our recorded PPTN neurons in primates responded differentially to a visual stimulus with dependent on motivational state.…”
Section: Possible Source Of the Fixation Target Responsecontrasting
confidence: 76%
See 2 more Smart Citations
“…There have been only a few studies examining visual responses of PPTN neurons. Pan & Hyland (2005), reported visual responses of PPTN neurons in rats, which had a mean response latency to the onset of a light stimulus of 70 ms, but they observed no variable visual responses for reward prediction (Pan & Hyland, 2005). In contrast to these results, a population of our recorded PPTN neurons in primates responded differentially to a visual stimulus with dependent on motivational state.…”
Section: Possible Source Of the Fixation Target Responsecontrasting
confidence: 76%
“…The prolonged response of the fixation target neurons indicates that they may maintain the signals of the predicted reward from the time of cue presentation until the reward delivery neurons signal the actual reward magnitude. This study revealed that the strong excitatory inputs exerted by the PPTN on midbrain dopamine neurons (Mena-Segovia et al, 2004;Pan & Hyland, 2005;Winn, 2006) convey the memory of the predicted reward and the signals of the actual reward, two essential elements needed for computing the reward prediction error. The high information capacities of the fixation target and reward delivery neurons to signal the reward magnitude may help the dopamine neurons to accurately compute the reward prediction error and to efficiently execute reinforcement learning.…”
Section: Computation Of Reward Prediction Error Signal In Dopamine Nementioning
confidence: 99%
See 1 more Smart Citation
“…Schultz and others have shown that presentation of reward-related signals induces transient burst firing in DA neurons only when the reward-related signal is unpredicted (ie novel) (Schultz, 1998). Furthermore, the PPTg has been shown to respond to sensory stimuli (Grunwerg et al, 1992;Reese et al, 1995) and it has been suggested that this region may be involved in signal detection independent of its behavioral salience (Pan and Hyland, 2005); therefore, the PPTg may be involved in detecting a signal with the hippocampus evaluating its novelty (Lisman and Grace, 2005). Since the computation of novelty requires the comparison of incoming information with stored memories, this likely occurs in the hippocampus (Knight, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, vSub activation excites Acb projection neurons that inhibit ventral pallidal GABAergic afferents to the VTA, thereby releasing DA neurons from a tonic inhibitory influence (Floresco et al, 2001). In contrast, the pedunculopontine tegmental nucleus (PPTg) is a glutamatergic/cholinergic region driven by a number of limbic afferents, including the prefrontal cortex, bed nucleus of the stria terminalis and central nucleus of the amygdala (Semba and Fibiger, 1992), and has been shown to be activated by auditory (Pan and Hyland, 2005;Reese et al, 1995), visual (Pan and Hyland, 2005) and somatosensory stimuli (Grunwerg et al, 1992). The PPTg was found to also directly regulate burst firing of DAergic neurons (Floresco et al, 2001;Lokwan et al, 1999).…”
Section: Introductionmentioning
confidence: 99%